Do journals contribute to the international publication of research in their field? A bibliometric analysis of palliative care journal data. (April 2020) - Walshe, Catherine; Ahmed, Faraz; Preston, Nancy
Background: Research is important internationally, impacting on health service provision and patient benefit. Journals play an important dissemination role, but there may be geographical bias, potentially affecting access to evidence. Aim: To understand if there is a relationship between the continent of journals and that of contributing authors. Design: Bibliometric analysis of journal citation report data (June 2018). Odds ratio of association of an author being from region, region of journal publication, publication model and the number of papers. Setting: Journals specialising in palliative care research, with an impact factor above the median impact factor for their most common indexing category. Results: Five journals: three published in Europe ( Palliative Medicine, BMJ Supportive and Palliative Care, and BMC Palliative Care ) and two in North America ( Journal of Pain and Symptom Management and Journal of Palliative Medicine ). Authors were from 30+ countries, but mostly North America (54.18%) or Europe (27.94%). Preliminary sensitivity tests show that the odds of an author being from a North American institution increase 16.4 times ( p < 0.01; 95% confidence interval: 12.9, 20.8) if the region of journal publication is North America. The odds of an author being from a European institution is 14.0 times ( p < 0.01; 95% confidence interval: 10.9, 17.9) higher if the region of journal publication is Europe. Conclusion: Publishers, editors and authors are concentrated in North America or Europe. North American authors are more present in North American journals and European authors in European journals. This polarised approach, if replicated across readerships, may lead to research waste, duplication, and be sub-optimal for healthcare development.